The Care Certificate Evaluation: an overview - Argyle, Elaine; Thomson, Louise; Khan, Zaynah; Arthur, Tony; Maben, Jill; Schneider, Justine M.; Wharrad, Heather (2017)
BACKGROUND: Front line care workers play a key role in health and social care provision for older people and this has been reflected in training innovations aiming to improve the care provided by these workers. One recent training initiative has been the Care Certificate, which was fully launched in England in April 2015 and which aims to provide a consistent and transferable approach to this training. However, little is currently known about the patterns of implementation adopted by care organisations or about the perceptions of the Care Certificate held by care providers and by those in receipt of this care. AIMS: In order to address these issues and to optimise its impact, the implementation of the Care Certificate is being evaluated through an 18 month national study funded by the Department of Health Policy Research Programme. Project Reference Number PR-R14-0915-12004. METHODS: This study includes a telephone survey of care organisations in England as well as qualitative explorations of the views and experiences of the Care Certificate held by care providers and care receivers. This poster provides an overview of this national evaluation, highlighting why it is needed, how it is being carried out as well as summarising some of its preliminary findings.